Recent Nuclear Astrophysics Measurements using the TwinSol Separator. (July 2016) - Bardayan, D W; Ahn, T; Allen, J; Becchetti, F D; Blackmon, J C; Brodeur, M; Frentz, B; Gupta, Y K; Hall, M R; Hall, O; Henderson, S; Hu, J; et al.
Abstract: Many astrophysical events, such as novae and X-ray bursts, are powered by reactions with radioactive nuclei. Studying the properties of these nuclei in the laboratory can therefore further our understanding of these astrophysical explosions. The TwinSol separator at the University of Notre Dame has recently been used to produce intense (∼10 6 pps) beams of 17 F. In this article, some of the first measurements with these beams are discussed.